SYNE1 Exonic Variant rs9479297 Contributes to Concurrent Hepatocellular and Transitional Cell Carcinoma Double Primary Cancer - Yu-De Chu; Kwong-Ming Kee; Wey-Ran Lin; Ming-Wei Lai; Sheng-Nan Lu; Wen-Hung Chung; See-Tong Pang; Chau-Ting Yeh (Biomedicines, 2021)
Unexpected high risk of synchronous/metachronous hepatocellular carcinoma (HCC) and transitional cell carcinoma (TCC) co-occurrence has been discovered previously. Here, we searched for genetic variation contributing to the co-occurrence of this double primary cancer (DPC). Using targeted exome sequencing, a panel of variants associated with concurrent DPC was identified. However, only a nonsynonymous variant within the Spectrin Repeat Containing Nuclear Envelope Protein 1 (SYNE1) gene was associated with DPC occurrence (p = 0.002), compared with that in the healthy population. Further independent cohort verification analysis revealed that the SYNE1-rs9479297-TT genotype (versus TC + CC genotypes) was enriched in patients with DPC, compared with that in those with TCC alone (p = 0.039), those with HCC alone (p = 0.006), those with non-HCC/non-TCC (p < 0.001), and healthy population (p < 0.001). SYNE1 mRNA expression reduced in both patients with HCC and TCC, and its lower expression in HCC was associated with shorter recurrence-free (p = 0.0314) and metastasis-free (p = 0.0479) survival. SYNE1-rs9479297 genotypes were correlated with tissue SYNE1 levels and clinical outcomes in HCC patients. Finally, SYNE1 silencing enhanced the cell proliferation and migration of HCC/TCC cells. In conclusion, SYNE1-rs9479297 genotypes were associated with HCC/TCC DPC co-occurrence and correlated with SYNE1 expression, which in turn contributed to HCC/TCC cell proliferation and migration, thereby affecting clinical outcomes.